2002
DOI: 10.1016/s0002-9440(10)64417-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin Reduces Osteoclast Numbers and Prevents Bone Erosion in Collagen-Induced Arthritis

Abstract: Rheumatoid arthritis is characterized by progressive synovial inflammation and joint destruction. While matrix metalloproteinases (MMPs) are implicated in the erosion of unmineralized cartilage, bone destruction involves osteoclasts, the specialized cells that resorb calcified bone matrix. RANK ligand (RANKL) expressed by stromal cells and T cells, and its cognate receptor, RANK, were identified as a critical ligand-receptor pair for osteoclast differentiation and survival. A decoy receptor for RANKL, osteopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
181
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(195 citation statements)
references
References 42 publications
12
181
0
2
Order By: Relevance
“…Third, serum parameters of bone metabolism reflect an increased bone resorption as the major cause for RA-associated generalized bone loss (14,(19)(20)(21). And, fourth, the roles of RANKL-RANK interaction and osteoclasts in local bone erosion of inflammatory arthritis and the therapeutic efficacy of RANKL/RANK blockade in this respect have been increasingly established (29)(30)(31)(32)(33)(34)(44)(45)(46), providing evidence of a propensity for osteoclasts to become activated in RA. The data reported herein support the concept that hTNFtg mice experience not only a severe destructive arthritis, but also a severe generalized bone loss as a consequence of TNF overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, serum parameters of bone metabolism reflect an increased bone resorption as the major cause for RA-associated generalized bone loss (14,(19)(20)(21). And, fourth, the roles of RANKL-RANK interaction and osteoclasts in local bone erosion of inflammatory arthritis and the therapeutic efficacy of RANKL/RANK blockade in this respect have been increasingly established (29)(30)(31)(32)(33)(34)(44)(45)(46), providing evidence of a propensity for osteoclasts to become activated in RA. The data reported herein support the concept that hTNFtg mice experience not only a severe destructive arthritis, but also a severe generalized bone loss as a consequence of TNF overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoprotegerin (OPG) is a naturally occurring decoy receptor of RANKL and blocks its action by preventing RANKL-RANK interaction (28). The efficacy of OPG and other forms of blocking RANK signaling to inhibit local bone erosion without reducing inflammation has been demonstrated in different animal models of arthritis (29)(30)(31)(32)(33)(34). We recently demonstrated that OPG inhibits local bone erosion in the joints of mice transgenic for human TNF (hTNFtg), which mimics human RA by the spontaneous development of a progressive and destructive polyarthritis (31).…”
mentioning
confidence: 99%
“…It was previously shown that OPG expression on macrophage-type synovial lining cells as well as endothelial cells is deficient in RA patients with active synovitis (18). OPG administration reduced osteoclast numbers and bone erosions in collagen-induced arthritis (15).…”
mentioning
confidence: 97%
“…The effects are mediated through RANKL, a member of the tumor necrosis factor superfamily that is expressed on osteoblast/stromal cells and activated T cells (13,14). RANKL exists as a membrane-bound peptide, a soluble fragment cleaved from the cell surface, and a secreted protein (15). Osteoprotegerin (OPG) is a secreted decoy receptor that binds and thereby inactivates RANKL (16).…”
mentioning
confidence: 99%
“…Although there has been controversy regarding the cellular mechanisms involved in the pathogenesis of focal articular bone erosions, multiple lines of evidence now support the concept that this process is dependent on osteoclasts. The most compelling data are derived from recent studies in 3 animal models of inflammatory arthritis with different pathogenic mechanisms in which inhibition of osteoclast formation and activation resulted in marked attenuation of focal bone erosions (1)(2)(3). In these studies, the biologic activity of RANKL, an essential factor for osteoclast differentiation, was blocked with osteoprotegerin (OPG), a soluble RANKL receptor.…”
mentioning
confidence: 99%